O crime de descaminho: um desafio para a cooperação internacional, no âmbito da integração latino-americana ou uma prática passível de descriminalização? - Umpierre, Camila Machado (2007)
This research approaches the embezzlement crime, foreseen in the Brazilian criminal legislation, article 334, second part of the native Criminal Code, analyzing it under the Criminal Law optics, of the beddings tributaries and customs officers involved countries in the regional integration process and, finally, on the basis of the principles and objectives of the Common Market of the South (Mercosul). It is possible to affirm that today the practical one of the embezzlement is constant between the Latin American countries, unchaining a reality that worry the involved States, therefore points with respect to a social reality, a time that people also survive of the commerce of misguided products and because she implies reduction in the collection tax. To analyze this context, the proposal of this work is to study the embezzlement crime as being, or a challenge for the involved countries in the Latin American integration (firmed in the Asunción Treated), or one decriminalization act. The States members of the Mercosul had firmed commitments in the direction to eradicate this criminal act, understanding that such behavior harms the countries fiscal collection, however, what it is seen is the increase of the incidence of the misdemeanor. On the other hand, leaving of the premise of that the Mercosul is a project in progress and that its objectives (a time materialize) imply in customs union, it exempts commerce and harmonization tax or unification, the embezzlement crime appears in history as one decriminalization act. It was approached, also, the objective of the Criminal Law as legal properties guard, standing out that this must be seen as last ratio and not as the State illness remedy. Thus, one searched to analyze the mbezzlement crime in an interdisciplinary context, in agreement with the integration principles.